Isolasi dan Identifikasi Senyawa Flavonoid pada Tanaman - Audi Ichsani; Christina Febiola Lubis; Lestari Mahardika Urbaningrum; Nurma Dwi Rahmawati; Sridevi Anggraini (Syntax Corporation Indonesia, 2021)
Isolation of flavonoid compounds can be done in various stages. In this study, a literature study was done to determine the procedure for the Isolation and Identification of Flavonoid Compounds. The procedure usually begins with a phytochemical test (screening) first. Flavonoid phytochemical tests can be done with various types of tests, Bate Smith-Matcalfe test, 10% NaOH test, and Wilstatter test. It can be done with all of the tests or just one of them. The first step is extraction with a suitable solvent. The suitable solvents for the isolation of flavonoid compounds are polar and semi-polar solvents. Extraction of plant compounds for isolated flavonoid compounds used the maceration method. Maceration carried out for 72 hours while stirring every 24 hours. After that the extract was concentrated with a rotary vacuum evaporator. The next step is fractionation. For the fractionation of isolated flavonoid compounds, it can be done by the methods of Liquid-Liquid Extraction, Vacuum Liquid Chromatography, Column Chromatography, and Thin Layer Chromatography. Solvents that can be used in this step vary, depending on the method. Then, isolate be monitored to determine the type of flavonoid contained in the isolate. The methods that can be used in this step are UV-Vis Spectrophotometer, HNMR, and FTIR spectrophotometer. You can use one method or two methods.